INTEGRATED APPROACH TO AESTHETIC EDUCATION OF SCHOOLCHILDREN IN THE PEOPLE’S REPUBLIC OF CHINA - Ionova, Olena; Luparenko, Svetlana; Lakhmotova, Yuliia (Educological discourse, 2020)
The article is dedicated to revelation of the peculiarities of integrated approach in the process of schoolchildren’s aesthetic education in the People’s Republic of China. The possibilities of using art while teaching different subjects (Mathematics, different languages, Literature, History etc.) have been outlined. The Chinese pedagogues underline the close connection of Mathematics and Music. It provides opportunities to learn fractional nature of the notes, feel the rhythm of the music, relate harmony, intervals, melody and notes to whole numbers, proportions, arithmetic operations, logarithms, Geometry and Trigonometry. The authors have pointed out that aesthetic subjects (music, art, theatre) are also closely connected in educational process of schools. The characteristic feature of schoolchildren’s aesthetic education in the People’s Republic of China is taking into account the regionality (differences in development of art depending on the region of the country). It is due to different historical, socio-economic and cultural factors of development of different regions in China. The regionality strengthens the connection of arts with History, Economics and Geography and helps schoolchildren to understand the significance and differences of regional music in China, to learn various Chinese musical instruments, folk lullabies and to investigate the important characteristic features of the Chinese music. So, schoolchildren’s aesthetic education in China has a strong national basis: art is connected with national expression, development of musical traditions, nature and mental aesthetic ideas.